The Guardian - Lewis, Beverly, 1949- (Minnesota Bethany House, 2013)
After schoolteacher Jodi Winfield finds a little girl on the side of the road, she delves into the isolated community of the Lancaster Old Order Amish to find answers.
Keywords: Foundlings -- Fiction; Amish -- Fiction; Lancaster County (Pa.) -- Fiction; Christian fiction